Recaudación de Créditos otorgados a Socios de la Cooperativa de Ahorro y Crédito “San Antonio” del Cantón Babahoyo, en el Periodo 2021. - Avilés Flores, Lilia Lisseth (2022)
The San Antonio Savings and Credit Cooperative of the Babahoyo Canton is a non-profit organization created to serve its members. This institution provides credits and grants credit solutions to members, offering training to the respective custodian of working capital that they deposit daily in said cooperative, but in turn this activity becomes a big problem as the collection management of the members is not carried out credits that have been issued causing liquidity and economic problems of the Cooperative, it is for this reason that the situation of the past due portfolio of the Cooperative and its recovery process from the granting of credits to clients is analyzed, it is difficult to that the loan officers recover the overdue portfolio at a relevant time.